2016
DOI: 10.1007/s00256-016-2427-2
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and efficacy of fluoroscopy-guided pars interarticularis injections on immediate and short-term pain relief

Abstract: Over 92 % of fluoroscopically guided injections for symptomatic spondylolysis are technically successful with minimum fluoroscopic time, resulting in statistically significant pain reduction immediately post-injection and a trend in pain reduction 1-week post-injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…The injections are made directly into the pseudarthrosis in the pars, given the direct site of pain generation is the pars fracture. Kershen et al [ 56 ] retrospectively reviewed 121 patients undergoing pars injection with the aim of determining the accuracy and short-term efficacy of fluoroscopy-guided steroid/anesthetic injections for symptomatic pars defects. Patient-reported VAS scores were used to measure outcomes.…”
Section: Spondylolysis and Spondylolisthesismentioning
confidence: 99%
“…The injections are made directly into the pseudarthrosis in the pars, given the direct site of pain generation is the pars fracture. Kershen et al [ 56 ] retrospectively reviewed 121 patients undergoing pars injection with the aim of determining the accuracy and short-term efficacy of fluoroscopy-guided steroid/anesthetic injections for symptomatic pars defects. Patient-reported VAS scores were used to measure outcomes.…”
Section: Spondylolysis and Spondylolisthesismentioning
confidence: 99%
“…In one study by Wald et al, 38% of patients experienced pain relief at 2 months post procedure. 112 Kershen et al 111 , on the other hand, showed only 19% of patients with greater than 50% pain reduction 1-week post injection. Nevertheless, pars interarticularis has shown to be a safe procedure and may be valuable in the selection of patients with symptomatic spondylolysis for surgical repair.…”
Section: Pars Defect Injectionmentioning
confidence: 98%
“…Injections are often made up of an anaesthetic and corticosteroid combination and are directly targeted into the spondylolytic area under fluoroscopic or CT guidance. 111,112 CT-guided injections currently however have not been well described. Under fluoroscopy, the patient is placed in a prone position with a pillow placed below the lower abdomen to minimise lumbar lordosis.…”
Section: Pars Defect Injectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most patients are successfully managed conservatively, with surgery reserved for the 9-15% of cases that remain symptomatic after conservative care [29]. Because the condition can be asymptomatic, diagnostic steroid and anesthetic injection can be helpful to confirm the spondylolysis as the source of the patient's pain prior to surgery [34].…”
Section: Lower Lumbarmentioning
confidence: 99%